ダイ8ジ ナンキョク カンソク 1966 1967 ノ トキ サイシュウ サレタ ヒョウメン カイスイチュウ ノ フユウ ケンダクブツ ノ テツ オヨビ マンガン ガンユウリョウ - 兼島, 清; カネシマ, キヨシ; 与那原, 峯子; ヨナハラ, ミネコ; KANESHIMA, Kiyoshi; YONAHARA, Mineko (国立極地研究所, 1970)
P(論文) The contents of iron and manganese in participate matter separated with millipore filter from surface waters sampled in 1966-1967 during the cruise of research vessel FUJI to Antarctica have been analyzed. Iron was determined by absorption spectrophotometric measurement of the complexes formed in the presence of bathophenanthroline. Oxidation of leucomalachite green with periodate in the presence of manganese has been used for the quantification of submicrogram amounts of manganese. The results indicated that the horizontal distribution of iron and manganese contents was low in the western Pacific and in the northern part of the Indian Ocean, and high in the southern part of the Indian Ocean and in the Antarctic Ocean. The concentration of iron in particulate matter from surface water of all oceans and seas ranged from 0.003 to 0.140 μg-at/l with an average value of 0.038 μg-at/l, and concentration of manganese ranged from 0.0005 to 0.0098 μg-at/l with an average value of 0.0031 μg-at/l. A positive correlation was ascertained between the amount of iron and that of manganese contained in the particulate matter. Since the horizontal distribution of chlorophyll-a generally agreed with the distribution of iron and manganese in the particulate matter collected in these oceans, and since the iron contents increased almost linearly with an increase in the manganese contents in the plankton, it is suggested that contents of iron and manganese in the parcitulate matter are affected by the plankton. departmental bulletin paper